(untitled) - Bernard, Scott A. ([Bloomington, Ind.], 2005)
This book provides a cursory treatment of a deep subject. At barely 250 pages of main body text--and they are small pages at that, set in a generous type--there is no room to go into detail on much of anything.
Keywords: Management information systems,System design,Information technology,Quản trị hệ thống thông tin,Thiết kế hệ thống,Công nghệ thông tin; Management,Quản trị